Anti-Inflammatory Activity of 4-((1R,2R)-3-Hydroxy-1-(4-hydroxyphenyl)-1-methoxypropan-2-yl)-2-methoxyphenol Isolated from Juglans mandshurica Maxim. in LPS-Stimulated RAW 264.7 Macrophages and Zebrafish Larvae Model - Su-Hyeon Cho; SeonJu Park; Hoibin Jeong; Song-Rae Kim; Myeong Seon Jeong; Miri Choi; Seung Hyun Kim; Kil-Nam Kim (MDPI AG, 2021)
Juglans mandshurica Maxim., a traditional folk medicinal plant, is widely distributed in Korea and China. In our previous study, we isolated a new phenylpropanoid compound, 4-((1R,2R)-3-hydroxy-1-(4-hydroxyphenyl)-1-methoxypropan-2-yl)-2-methoxyphenol (HHMP), from J. mandshurica. In the present study, we evaluated the anti-inflammatory activity of HHMP on lipopolysaccharide (LPS)-stimulated RAW 264.7 cells and zebrafish larvae. HHMP significantly inhibited LPS-induced nitric oxide (NO) and prostaglandin E2 production in a dose-dependent manner. Moreover, HHMP treatment considerably suppressed LPS-induced expression of inducible nitric oxide synthase and cyclooxygenase-2. We also demonstrated the mechanisms of HHMP inhibition of inflammatory responses in LPS-stimulated RAW 264.7 cells via Western blot analysis and immunofluorescence staining. Furthermore, HHMP significantly inhibited NO production in LPS-stimulated zebrafish larvae. Consequently, we established that HHMP significantly inhibited the LPS-induced activation of NF-κB and MAPK and the nuclear translocation of p65 in RAW 264.7 cells. Taken together, our findings demonstrate the effect of HHMP on LPS-induced inflammatory responses in vitro and in vivo, suggesting its potential to be used as a natural anti-inflammatory agent.